2014
DOI: 10.4103/0976-9668.136167
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of cedarwood oil and xylene in hematoxylin and eosin staining procedures: An experimental study

Abstract: Background:Xylene is used as a clearing agent in hematoxylin and eosin (H and E) staining of tissue sections in routine histopathology based diagnosis. However, the hazards associated with exposure to xylene are of concern. Numerous solutions mainly essential oils have been evaluated in the past as clearing agents, which can possibly be substituted for xylene during the routine tissue processing.Aim:The aim of this study is to compare the efficacy of essential oil (cedarwood oil), as a possible replacement for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 4 publications
0
12
1
2
Order By: Relevance
“…Cedar wood oil and Coconut oil were less effective to assess cellular architecture compared to Xylene and Dish wash liquid. This was not in accordance with study conducted by Sudip Indu et11 12…”
contrasting
confidence: 75%
“…Cedar wood oil and Coconut oil were less effective to assess cellular architecture compared to Xylene and Dish wash liquid. This was not in accordance with study conducted by Sudip Indu et11 12…”
contrasting
confidence: 75%
“…Cedarwood oil at 8%, being nontoxic, noninflammable, nonhazardous, and easy to handle, produced good quality staining with sufficient clarity and uniformity of staining in comparison with xylene. [12]…”
Section: Discussionmentioning
confidence: 99%
“…used 8% cedarwood oil to produce quality staining with sufficient clarity and uniformity. [ 16 ] Pandey et al . used DWS as an alternative to xylene and alcohol in H and E staining and found that 84% sections which were routinely stained with xylene and 84% sections with liquid DWS were adequate for diagnosis.…”
Section: Discussionmentioning
confidence: 99%